UTILIZATION OF AREN (Arenga pinnata Merr.) SAWMILLING WASTE FOR EDIBLE MUSHROOM CULTIVATION MEDIA - Djarwanto, Djarwanto; Suprapti, Sihati (Indonesian Journal of Forestry Research, 2016)
The utilization of unproductive aren (Arenga pinnata) for timber produces waste i.e. sawdust and core. The waste containing of lignocellulosic materials was studied for cultivation medium of edible mushroom. The sawdust was supplemented with rice bran, CaCO3, gypsum, fertilizers, and distilled water. This composite medium was then sterilized in an autoclave on 121 â°C, in pressure of 1.5 atmosfir for 30 minutes. After cooling the medium was inoculated with pure culture of four different mushrooms species and incubated in a special room. Biological conversion efficiency (BE) was calculated based on the weight of the fresh mushroom yield to the weight of dry substrate and presented in percentage. Other waste in the form of sawn timber core was cut into 10 cm in wide 5 cm in thick and 120 cm in length, then directly inoculated with six species of mushrooms through drilled holes, then were slanted on bamboo supporter in an angle of around 60â° in a hut made of bamboo. The mushroomâs was harvested daily after the mature fruiting body grown. Results showed that the material supplementation on sawdust most likely to improve the mushrooms yield. Found that the BE values are 21.97-89.45 % (for Pleurotus flabellatus), 15.36-105.36 % (for P. ostreatus), 63.88-76.86 % (for P. sajor-caju), and up to 62.88% (for Lentinula edodes). The average yield from a piece of sawn timber core was 210g (for P. ostreatus), 368g (P. flabellatus), 331g (P. sajor-caju), and 48g (Auricularia polytricha), however, P. cystidiosus and L. edodes on aren stem core were fail to grow.